2022
DOI: 10.3390/antiox11010121
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera and Centella asiatica Extracts Ameliorate Behavioral Deficits in an In Vivo Drosophila melanogaster Model of Oxidative Stress

Abstract: Due to an increase in the aging population, age-related diseases and age-related changes, such as diminished cognition and sleep disturbances, are an increasing health threat. It has been suggested that an increase in oxidative stress underlies many of these changes. Current treatments for these diseases and changes either have low efficacy or have deleterious side effects preventing long-time use. Therefore, alternative treatments that promote healthy aging and provide resilience against these health threats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…To determine whether WS provides resilience against these age-related changes, we used the fast phototaxis test, in which the flies have to locate and run toward a light source after being startled. We previously showed that supplementing standard food with 0.5 mg/g or 2.0 mg/g of the WS water extract improved the performance of the Drosophila sniffer mutant that shows increased oxidative damage [ 40 ] in this assay [ 41 ]. We therefore also initially used these concentrations to assess whether this had positive effects on the age-related decline in performance.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether WS provides resilience against these age-related changes, we used the fast phototaxis test, in which the flies have to locate and run toward a light source after being startled. We previously showed that supplementing standard food with 0.5 mg/g or 2.0 mg/g of the WS water extract improved the performance of the Drosophila sniffer mutant that shows increased oxidative damage [ 40 ] in this assay [ 41 ]. We therefore also initially used these concentrations to assess whether this had positive effects on the age-related decline in performance.…”
Section: Resultsmentioning
confidence: 99%
“…or the supplemented food was also given during the three days of stress induction during the rest period at night (continuous treatment, con., Figure 2 A). In previous experiments, testing CAW in a Drosophila model of oxidative stress, we found that it had a protective effect at a dose of 10 mg/g of food and we therefore used this dose to test for beneficial effects on depression [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…To address suboptimal practice, interventions should emphasize the importance of sleep hygiene and provide practical strategies to enhance sleep-related behaviors. Behavioral interventions, such as stimulus control therapy, can be introduced to modify practice associated with poor sleep hygiene 31 . Educational materials should be tailored to address specific problematic practice identified in the study, promoting realistic and feasible alternatives that align with evidence-based recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The item that gauges the consistency of participants' daily schedules highlights a favorable practice linked with sleep hygiene. 31 . Educational materials should be tailored to address specific problematic practice identified in the study, promoting realistic and feasible alternatives that align with evidence-based recommendations.…”
Section: Path Analysismentioning
confidence: 99%